Upaya meningkatkan kemampuan Motorik Halus Melalui Media Busy Book - Irma Safitri; Moh Fauziddin; Masrul Masrul (Jurnal Pendidikan Tuntas, 2024)
This research was motivated by the results of observations at the Kemala Bhayangkari Bangkinang City Kindergarten regarding children's fine motor skills that had not developed optimally. So improvements need to be made through busy book media. The problem in this research is that children have difficulty holding a pencil, children lack concentration, are not precise and neat and lack patience in carrying out learning activities related to fine motor skills, children are not able to follow the pattern lines ordered by the teacher, children have difficulty recognizing colors. This research aims to improve the fine motor skills of class A children at the Kemala Bhayangkari Bangkinang City Kindergarten through busy book media. The subjects in this study were 15 children consisting of 8 girls and 7 boys. This research uses classroom action research methods. This research consisted of two cycles and each cycle was held in 2 meetings. The data collection techniques used are observation and documentation. From the calculations carried out, it can be seen that the percentage of children's fine motor skills has increased from the initial condition of the number of children with the Not Yet Developed (BB) criteria of 59.9%. In cycle I the criteria for Not Yet Developed (BB) was reduced to 17.9%. In cycle II, the criteria for Not Yet Developed (BB) were reduced again to 1.65%. This proves that busy book media can improve children's fine motor skills at the Kemala Bhayangkari Bangkinang City Kindergarten.